Smallwood Interview 10B - Memorial University of Newfoundland. Educational Television Centre (Memorial University of Newfoundland. Educational Television Centre, 1983)
Robert Pitt interviews Joseph (Joey) Smallwood. Mr. Smallwood recalls the great diffculty of Depression years in Newfoundland and the riot of 1932, which began with a march on the Colonial Building, where the premier, Richard Squires was trapped.